PEMBELAJARAN BAHASA ARAB BERBASIS KURIKULUM MERDEKA DENGAN PENDEKATAN INDUKTIF DI MTSN 1 KOTA KEDIRI - Amaliyah, Rizkiyatul; Sulthoni, Annisa Zahro Putri; Putri, My Love Faizah; Ridwan, Ridwan (Al-Fakkaar, 2025)
This article reviews the independent curriculum Arabic learning process using an inductive approach for class VII at MTsN I Kediri City and students' perceptions of this learning. This research used a descriptive qualitative method with data collection techniques in the form of direct observation and written interviews with 32 class VII students at MtsN I Kediri City. The results of this research show that learning Arabic using an inductive approach involves the stages of muqoddimah, 'ardh, rabth, istinbath al-qoidah, and at-tathbiq. The process begins with greetings and prayers, followed by motivation, mufrodat singing, and a review of previous material. The teacher explains the material through examples, then students discuss in groups to conclude the rules, then the lesson closes with checking understanding, giving assignments, notification of upcoming material, and prayer. There are two student perceptions of the inductive approach, namely positive and negative. The positive response was proven by the results of student questionnaire which showed that inductive learning was clear, understandable and enjoyable. Meanwhile, negative responses were shown by the responses of several students that they could not understand Arabic material quickly, which made it difficult to do assignments. There are also students who lack focus and are sleepy during Arabic lessons. With these two responses, adjustments in teaching methods are very necessary for teachers to overcome challenges and increase the effectiveness of learning for all students.